Penggunaan Antigen Mycoplasma gallisepticum Freeze-Thawing dalam Teknik Enzyme-Linked Immunosorbent Assay - Faidah Rachmawati Rachmawati; I Wayan Teguh Wibawan; Ni Luh Putu Ika Mayasari (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Chronic Respiratory Disease (CRD) is a bacterial infection in chickens caused by Mycoplasma gallisepticum. CRD may result in economic loss in the livestock industry, decreasing of egg production and feed efficiency, increasing of medication costs, downgrading of carcass and egg qualities. The aim of this study was to develop the Enzyme-Linked Immunosorbent Assay (ELISA) kit for detecting antibodies of M. gallisepticum using freeze-thawing antigens. The cut-off point was determined by S/N method. Chicken antiserum againts M. gallisepticum was collected every week on 1st – 6th week post immunization of whole cell antigen of M. gallisepticum. Optimization of antigen, serum and conjugate were 10 μg/ml protein concentrations, 1:800 serum dilution and 1:10000 conjugate dilution. The validation results on developed ELISA kit (MyGELISA) analyzed by ROC curve using MedCalc statistical software revealed that developed ELISA kit (MyGELISA) had 100% sensitivity and 86.21% specificity with 95% confidence interval. The results of RSA, MyGELISA and commercial ELISA kit showed antibodies positif againts M. gallisepticum. In conclusion, MyGELISA using freeze-thawing antigen can be used to detect antibodies of M. gallisepticum.